Gender Differences in Coping Strategies for Marital Stress: The Role of Marital Satisfaction and Implications for Counseling - Hidayat, M. Bobby; Toybah, Nur (Acta Psychologia, 2025)
This study explores gender differences in coping with marital stress, aiming to understand how men and women manage relational challenges. Using a mixed-methods approach, the research examines the coping strategies employed by couples experiencing marital stress, focusing on problem-focused, emotion-focused, and avoidant coping behaviors. The findings reveal that men predominantly use problem-focused coping, concentrating on resolving issues, while women are more likely to engage in emotion-focused strategies, seeking emotional support and expressing feelings. Additionally, marital satisfaction was identified as a key factor influencing the effectiveness of coping strategies, with higher satisfaction associated with more adaptive coping behaviors. The study emphasizes the importance of tailoring marital counseling to address gender-specific coping preferences and enhancing relationship satisfaction to improve stress management. The research concludes by suggesting further studies, including longitudinal and cross-cultural research, to deepen the understanding of marital stress coping over time and across diverse contexts.